All Days 2002
DOI: 10.2118/78959-ms
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Acidic Oil Transportation By Emulsion In Water

Abstract: This paper sets out to demonstrate, at lab scale, the feasibility of the twomain phases of the process, namely the emulsification of a heavy Venezuelanacidic crude oil (ZUATA), and the subsequent breaking of the oil-in-wateremulsion. The heavy ZUATA crude can be emulsified directly by making use of thesurfactants naturally present in this rich acid oil. These potentialsurfactants, mainly represented by naphthenic acids, become effectiveemulsifiers when salified into naphthenate anions by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The second way is to "activate" the natural surfactants which are part of heavy crude oil composition: one can make these surfactants more hydrophilic by ionizing the acid functional groups carried by the fatty acids and asphaltenes (from low molecular weight species to carboxylic functions carried by asphaltenes) with a strong base like soda. Addition of strong bases is a well know process in enhanced oil recovery by decreasing interfacial tension to very low values [32][33][34][35][36][37][38]. The presence of natural saponifiable acids in some crudes may eliminate the need for expensive commercial surfactants.…”
Section: Application To Heavy Oil Transportationmentioning
confidence: 99%
See 1 more Smart Citation
“…The second way is to "activate" the natural surfactants which are part of heavy crude oil composition: one can make these surfactants more hydrophilic by ionizing the acid functional groups carried by the fatty acids and asphaltenes (from low molecular weight species to carboxylic functions carried by asphaltenes) with a strong base like soda. Addition of strong bases is a well know process in enhanced oil recovery by decreasing interfacial tension to very low values [32][33][34][35][36][37][38]. The presence of natural saponifiable acids in some crudes may eliminate the need for expensive commercial surfactants.…”
Section: Application To Heavy Oil Transportationmentioning
confidence: 99%
“…Ammonia can then be recovered and recycled [35]. Breaking these emulsions is a challenge for different reasons: -The density of heavy oil is very close to the density of water.…”
Section: Application To Heavy Oil Transportationmentioning
confidence: 99%
“…Because asphaltenes are surface-active, water-in-oil emulsions are formed when oil and water are stirred together, for instance, during the production processes. Many studies of these emulsions can be found in the literature. Very early, the oil−water interfacial properties in the presence of asphaltenes have been shown to be very peculiar, with long adsorption times and formation of rigid skins at the interface. The influence of pH has been studied on model emulsions with asphaltenes or on water−crude oil emulsions. ,, There are basically two ways to obtain oil-in-water emulsions: through the addition of water-soluble surfactants and/or the addition of bases to saponify amphiphilic molecules contained in the oil, making their compounds (such as naphthenic acids, asphaltenes, ...) more hydrophilic. The aim of the present study is to investigate, in more detail, the role of pH on interfacial properties of asphaltenes and asphaltene/surfactant mixtures at the oil/water interface and to study the relationship between interfacial properties and the stability of model emulsions as a function of pH.…”
Section: Introductionmentioning
confidence: 99%
“…(d) For diluted extra heavy oils with naphtha or lighter crude for transportation by pipeline API gravity is 19 and viscosity is <350 cP (∼ < 355 cSt) for Canada and 400 cP (∼420 cSt) for Venezuela …”
Section: Reports Of Crude Oil Viscosity Values For Transportationmentioning
confidence: 99%